Controlling Comitology Accountability in a Multi-Level System - Brandsma, G.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
Comitology is the most important form of multi-level governance in the EU. Member State and Commission actors together create roughly 2,500 executive acts per year amounting to half of all European laws. Using new European and national data, this books argues that its accountability has improved over time, but that unexpected gaps have emerged.
Keywords: European Union; Europe—Politics and government; Law—Europe.; International organization; Globalization; Political science; European Union Politics; European Politics; European Law; International Organization; Globalization; Political Science